Spontaneous rupture of seminoma in undescended testis with hemoperitoneum: a rare presentation. (19th April 2018) - Diwakar, Deepak Kumar; Wadhwani, Nikita; Pradhan, Ravi Shekhar; Verma, Ravi Prakash
Abstract : Cryptorchidism is associated with increased risk of malignancy and infertility. We present a case of a 30-year-old man who presented to the Emergency Department of our tertiary care hospital with spontaneous intra-abdominal rupture of the seminoma in undescended testis with hemoperitoneum. This is a rare presentation of seminoma and emphasises the importance of scrotal examination in young men presenting with acute abdomen. Surgical management is the definitive treatment and should be instituted as soon as possible, after appropriate resuscitation.